Quantifying source-specific intake risks of wheat cadmium by associating source contributions of soil cadmium with human health risk - Yanling Li (Elsevier, 2021)
Sources of cadmium (Cd) contamination of farmlands and the potential risk to human health via dietary intake of wheat Cd are of great concern to consumers. A source-specific risk assessment (SSRA) model, which combined a positive matrix factorization receptor model and spatial analysis with a health risk assessment model, was developed based on a wheat field investigation in northern China. It was used to estimate the daily intake risk from different sources of ingesting Cd from wheat. The mixed source of wastewater and residues from industrial activities and atmospheric deposition were identified as the dominant sources of Cd contamination. Wheat Cd uptake could be predicted reliably from the pH and total Cd concentration of field soil. Based on the predictive model of Cd transfer from soil to wheat, the SSRA model then linked sources to the Cd intake risk from wheat grain. Results showed that the mixed source and the atmospheric deposition source accounted for 52.8% and 29.3%, respectively, of the wheat Cd intake risk. In combination with the spatial analysis, the potential risk of Cd contamination in western and central eastern areas was mainly attributed to the mixed source of wastewater and industrial residues, whereas the risk in the northwestern area was associated mainly with atmospheric deposition. Regionalized risk management strategies, focusing on different sources, were proposed to minimize the Cd input to field cropping system and to mitigate health risk for local residents.